2021
DOI: 10.3390/ph14100962
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids in Fungal Infections: From Bench to Bedside

Abstract: Retinoids—a class of chemical compounds derived from vitamin A or chemically related to it—are used especially in dermatology, oncohematology and infectious diseases. It has been shown that retinoids—from their first generation—exert a potent antimicrobial activity against a wide range of pathogens, including bacteria, fungi and viruses. In this review, we summarize current evidence on retinoids’ efficacy as antifungal agents. Studies were identified by searching electronic databases (MEDLINE, EMBASE, PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Studies support the antifungal and immunomodulatory properties of retinoic acid, pointing to the possible therapeutic role of systemic retinoids in onychomycosis. [7][8][9][10][11][12][13] In the present study, we evaluated the efficacy of combined pulsed itraconazole/ acitretin therapy versus either agent alone in the treatment of different types of onychomycosis. The results of the present work revealed that 51.1% of the itraconazole only group (group A) showed mycological clearance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies support the antifungal and immunomodulatory properties of retinoic acid, pointing to the possible therapeutic role of systemic retinoids in onychomycosis. [7][8][9][10][11][12][13] In the present study, we evaluated the efficacy of combined pulsed itraconazole/ acitretin therapy versus either agent alone in the treatment of different types of onychomycosis. The results of the present work revealed that 51.1% of the itraconazole only group (group A) showed mycological clearance.…”
Section: Discussionmentioning
confidence: 99%
“…However, in nail psoriasis, acitretin does not accelerate the already enhanced nail growth by the pathological process of psoriasis, instead it normalises psoriatic hyperproliferation of nail bed keratinocytes, decreases subungual hyperkeratosis, and hence increasing access by antifungals, besides its immunomodulatory and fungistatic functions. [7][8][9][10][11][12][13][14][15]24 Therefore, patients having nail psoriasis with concomitant ony-…”
Section: Complete Cure (Both Mycological and Clinical) Was Noted In 20%mentioning
confidence: 99%
See 2 more Smart Citations
“…Animal models can circumvent these limitations [17][18][19]. Therefore, various animal models of Pneumocystis pneumonia have been developed in attempt to address pathogenesis, virulence, immune response, diagnosis, or therapy concerns [19][20][21][22][23][24]. However, a single model cannot answer all the aforementioned questions, which explains in part the great multiplicity of supports that have been developed so far.…”
Section: Introductionmentioning
confidence: 99%